2021
DOI: 10.3390/molecules26051365
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Aromatic Substitution of Polyfluoroarene to Access Highly Functionalized 10-Phenylphenothiazine Derivatives

Abstract: Nucleophilic aromatic substitution (SNAr) reactions can provide metal-free access to synthesize monosubstituted aromatic compounds. We developed efficient SNAr conditions for p-selective substitution of polyfluoroarenes with phenothiazine in the presence of a mild base to afford the corresponding 10-phenylphenothiazine (PTH) derivatives. The resulting polyfluoroarene-bearing PTH derivatives were subjected to a second SNAr reaction to generate highly functionalized PTH derivatives with potential applicability a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Notably, the same compound 4 was smoothly accessible via the HDF of 2,3,4,5-tetrafluorobenzonitrile (3b), which ascertained the trifluorinated structure at the 2-, 3-, and 5-positions (Entry 3). Doubling the catalytic amount to 2 mol% led to a complete conversion and selectivity within 1 h. These results indicated that the C-F bond at the para position of the substituent was rather susceptible to the reduction [40,41]. 9b, 98 1 Standard conditions: Substrate (0.5 mmol), 1 (5.0 × 10 −3 mmol), 1,2-dimethoxyethane (2.5 mL), H2O (2.5 mL), 30 °C.…”
Section: Resultsmentioning
confidence: 87%
“…Notably, the same compound 4 was smoothly accessible via the HDF of 2,3,4,5-tetrafluorobenzonitrile (3b), which ascertained the trifluorinated structure at the 2-, 3-, and 5-positions (Entry 3). Doubling the catalytic amount to 2 mol% led to a complete conversion and selectivity within 1 h. These results indicated that the C-F bond at the para position of the substituent was rather susceptible to the reduction [40,41]. 9b, 98 1 Standard conditions: Substrate (0.5 mmol), 1 (5.0 × 10 −3 mmol), 1,2-dimethoxyethane (2.5 mL), H2O (2.5 mL), 30 °C.…”
Section: Resultsmentioning
confidence: 87%
“…The electron-deficient PFB component also enhances the molecule’s susceptiveness to nucleophiles and is highly amenable to S N Ar reactions . Fluorine substitution reaction through nucleophilic substitution reaction is noticed in various compounds such as pentafluorobenzaldehyde, pentafluorobenzonitrile, octafluorotoluene, pentafluorophenol-substituted porphyrins, , pentafluorophenyl ester, pentafluoropyridine, and pentafluorobiphenyl …”
Section: Introductionmentioning
confidence: 99%
“…Diphenylamino, phenothiazinyl, phenoxazinyl, carbazolyl, and 9,9-dimethylacridinyl groups have been widely used as efficient aromatic and amino donor substituents in the molecular design of advanced D–A dyes. However, regarding the acceptor site, many reports have revealed that the introduction of fluorine atoms onto the aromatic ring of the D–A dyes using groups such as perfluorophenyl, cyano-substituted perfluorophenyl, or perfluorobiphenyl at the acceptor site instead of phenyl, substituted phenyl, or naphthyl groups is efficient for stabilizing the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) and for ICT (Figure ).…”
Section: Introductionmentioning
confidence: 99%